Failure Mode and Effect Analysis of Power Transformer Based on Cloud Model of Weight - Jianpeng Bian; Xiaoyun Sun; Jing Yang (Universitas Ahmad Dahlan, 2015)
As the key component of a power system, the power transformer directly impacts the reliability and safety of the system. Failure mode and effects analysis (FMEA) is a methodology used to analyze potential failure modes within a system and has been used extensively to examine the power transformer’s performance in various potential failure scenarios. However, the FMEA method has several flaws; for example, the non-differential analysis of evaluation index and the impossibility of evaluating the actual risk among risk priority number (RPN) values that on the surface are equal. The cloud model of weight incorporates the relative importance of index. This paper proposes applying FMEA based on the cloud model of weight to assess a power transformer for risk, and shows that this method can effectively overcome the defects of traditional FMEA assessment methods.